Simulation of suppression of vortex breakdown over delta wings by vortex filament method - Lewpiriyawong Nuttawut. (2008)
This study focuses on three-dimensional evolution of unperturbed and perturbed leading-edge vortices over delta wings. Since the vortex filament method can discretize the high vorticity-containing region of vorticity fields and track this discretization in a Lagrangian frame, it is chosen to simulate the core of the leading-edge vortices. The purpose of perturbing the vortex core is to delay or suppress vortex breakdown over delta wings.